INFLUENCE OF DIETARY ADDITIVES ON THE TECHNOLOGY OF SAUCES - ANTONENKO, АRTEM; BAL-PRYLYPKO, LARYSA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
food industry. Functional ingredients with increased protective and improved technological properties are increasingly used in food technologies. Such components include plant substances, in particular dietary fiber and plant phospholipids. Phospholipids are indispensable essential substances that enter the body only with food. They cannot be synthesized independently in the body, but they perform important functions: restoring cell membranes, participating in lipid metabolism and reducing the risk of cholesterol formation, and also ensuring the delivery of biologically active substances to cells. Gum arabic is a rich source of biologically active components, and its medicinal properties have already been recognized by official medicine. This study studied the effect of gum arabic and phospholipids in the recipe of red sauce on its rheological and physical properties. Samples of sauces with the replacement of 50% and 100% flour with gum arabic, as well as 30% animal fat with vegetable phospholipids, were developed. Changes in the effective viscosity and density of the resulting sauces were studied. It was found that at a shear rate of 0.3333 s-1, the viscosity of the control sample is 14.32 Pa·s, while samples with the replacement of 50% flour and 10 g of fat, as well as 100% flour and 10 g of fat showed 16.49 and 19.6 Pa·s, respectively. The replacement was accompanied by a slight increase in density. To substantiate the functional properties of sauces with vegetable additives, a study of their antioxidant activity (AOA) was conducted. It was found that the sauce with vegetable additives is able to "neutralize" 89% of radicals after 90 min in a model system. Adding such sauces to ready-made dishes, even in small quantities, increases their nutritional value and attractiveness. The influence of additives on the consumer characteristics of sauces that have a creamy and homogeneous consistency, a pronounced taste and aroma was studied. The conducted complex of studies allows us to confidently state that the use of affordable plant raw materials instead of traditional ingredients with high nutritional value can reduce energy value and expand the range of functional sauces for restaurant businesses.
Keywords: sauce; vegetable phospholipids; rheological characteristics; effective viscosity; antioxidant activity; organoleptic properties; protein-fat additive; gum arabic; dietary fiber; biotechnology